The Global Dynamics of Inequality (GINI) project: Analysing archaeological housing data - Bogaard, Amy (2023)
The GINI project investigates the dynamics of inequality among populations over the long term by synthesising global archaeological housing data. This project brings archaeologists together from around the world to assess hypotheses concerning the causes and consequences of inequality that are of relevance to contemporary societies globally.